Hak Khuluk Perempuan dalam Perspektif Fikih dan Keadilan Gender - Fitriyani, Fitriyani (STAINI Press, 2025)
This paper aims to explore the right of khuluk for women in the perspective of jurisprudence and gender justice. The main issues studied include: 1) What are the rights of women in the view of fiqh? and 2) How are women's khuluk rights reviewed from a gender perspective? This study uses a library research method by utilizing books, journal articles, and previous research reports, and is categorized as normative legal research that is analyzed descriptively. The results of the study show that the right of khuluk in the context of fiqh is a manifestation of gender equality in marriage relationships. If the husband has the right to divorce his wife through talaq, then the wife also has the right to